Biometry in Silicone Oil Filled Eyes. A Review - A. N. Kulikov; E. V. Danilenko; A. R. Kuznetsov (Oftalʹmologiâ, 2021)
The “gold standard” of modern vitreoretinal surgery is silicone oil tamponade of the vitreous cavity. The lens opacity development is in the list of complications of prolonged silicone oil eye filling (from 2 weeks to 2 years). Polydimethylsiloxanes hydrophobicity, direct contact with the front of the silicone bladder, macrophage and toxic reaction, trophic disturbances are the causes leading to the cataract initiation. This makes the problem of cataract surgery and preliminary intraocular lens calculation in silicone oil filled eyes before its removing very relevant as well as cloudy retina visualization and the necessity of minimization of number of operations through their combination. Certainly, the main error in IOL power calculation is associated with axial length measurement inaccuracy, as the most significant term of an equation. Silicone oil filled eyes biometry errors, and, consequently, postoperative refraction biases remain unresolved problem until now. To date authors report only 58 % of cases in which target refraction was achieved after combined surgery. Some researchers figure out that average calculation error after phacoemulsification with IOL implantation in avitreal eyes was 0.8 D despite of the optical biometry usage. Today it is represented by several methods: partial coherent interferometry, optical low-coherence reflectometry and optical coherence tomography, which are implemented in devices such as IOLMaster 500, Lenstar LS 900 and IOLMaster 700, which have their own characteristics and measurement accuracy. Their advantages as well as creation an accurate IOL calculation method for silicone oil filled eyes could reduce postoperative refraction error that outline significant medical and social problem.